Encapsulation of Magnetic Nanoparticles with Biopolymer for Biomedical Application - Chin, S.F.; Mohamed, Makha; Raston, Colin L. (IEEE, 2006)
Abstract—Magnetite nanoparticles were synthesized by coprecipitation of Fe2+ and Fe3+ with NH4OH using Spinning Disc Processing (SDP). Chitosan was then coated on the surface of magnetite nanoparticles using SDP. FTIR study and zeta potential measurement confirmed the absorption of chitosan unto the surface of magnetite nanoparticles. Transmission electron microscope (TEM) image showed that the particle sizes are in the range 10 – 200 nm.